(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
Visual media in concerts have turn into a must in recent years. Even though the viewer is very used to this resource, there is very little academic literature about it. This research focuses on the design that the filmmaker Derek Jarman made for the first tour of the Pet Shop Boys duo in 1989. The plastic elements used on the stage will be studied, with special interest in their projections. The result of this combination was a new show concept that opened the doors to another way of understanding pop music concerts.